Economic Populism in British and American Political Discourse A Comparative Analysis of Boris Johnson$1 (Bs and Donald Trump$1 (Bs Speechess - Zientara, Piotr; Zientara, Piotr; Sulowski, Stanislaw; Feder-Sempach, Ewa (Peter Lang, 2022)
This book presents the economic populism in British and American political discourse providing a current insight into the way Boris Johnson and Donald Trump communicate with the general public by raising fears over national security, immigration and technological advances. It shows how politicians asked for populism despite its poor economic record by using the same narrative of Conservatism. Unlike other books in the field which broadly discuss different aspects of populism, this book is the first in-depth analysis of economic populism containing political discourse studies. The recent populist discussion has started dominating the political arena in many countries. Hence, it seems that there is a need for a book that will explain the economic populism by showing its true nature.